Prenatal caprine milk oligosaccharide consumption affects the development of mice offspring - Thum, Caroline (Mol Nutr Food Res, 2016)
1. SCOPE: The composition of the gastrointestinal (GIT) microbiota, particularly in early life, influences the development of metabolic diseases later in life. The maternal microbiota is the main source of bacteria colonising the infant GIT and can be modified by dietary prebiotics. Our objective was to determine the effects of prenatal consumption of prebiotic caprine milk oligosaccharides (CMO) on the large intestine of female mice, milk composition, and offspring's development. 2. METHODS AND RESULTS: C57BL/6 mice were fed either a control diet, CMO diet, or galacto‐oligosaccharide diet from mating to weaning. From weaning, some pups nursed by CMO, GOS, and control‐dams were fed the control diet for 30 days. CMO or GOS‐fed dams had increased colon length and milk protein concentration compared to control‐fed dams. At weaning, pups from CMO‐fed dams had increased body weight and colon length and increased proportions of colonic Bifidobacterium spp compared to the pups from control‐fed dams. Thirty days after weaning, pups from CMO‐fed dams had increased visceral fat weight compared to pups from control‐fed dams. 3. CONCLUSION: Consumption of CMO by the dams during gestation and lactation improved the development of the pups, and the relative abundance of bifidobacteria and butyric acid in the colon, at weaning.